The marine angiosperms, seagrass - Bujang, Japar Sidik (Universiti Putra Malaysia Press, 2012)
Seagrasses are a group of marine flowering plants. They are under the sub-division of angiosperms classed within a family of the monocotyledonous plants, which also includes the freshwater aquatic macrophytes. Although totally submerged, seagrasses have all the structures of the terrestrial plants with a root system, a shoot system, a vascular system, and vegetative and sexual reproduction, with flowers fertilized by water borne pollen. These structures and functions are unique for plants in the sea. Seagrasses occur in many areas along the coast of Malaysia and although small in area, form a significant component of the coastal ecosystem besides mangroves and coral reefs. Our research group field studies revealed that even though are seagrasses patchy in distribution, they constitute one of the common coastal ecosystem types. Those areas that were studied were those accessible ones. Many more areas, far and wide particularly in the off-shore islands in the territorial waters of Sabah are the most likely environments where extensive seagrasses occur. The structure of seagrass ecosystem can vary from a few or patches of plants to extensive seagrass beds by two or more mixed species. These beds are dynamic and productive, attract diverse grazers and predators, and often these are commercially important species. In some coastal areas, seagrasses are service provider i.e., support livelihood of coastal communities that depend on fisheries which are linked directly or indirectly to the environment and production created by seagrasses. These intrinsic roles of seagrasses although have been recognized have not been afforded the same priority as the mangroves and corals. One reason could be that seagrass ecosystem has historically been neglected and not been well-studied. With the growing concern and interest, this important system is based on what have been studied should be communicated. In this respect, I am glad to have this opportunity to present this lecture personally than my numerous papers published on seagrasses alone could provide. In general, what are known about seagrasses in Malaysia? What differentiates seagrasses from other plants? Seagrasses together with seaweeds and phytoplankton form the important primary producers of a shallow marine environment. Seagrasses and seaweeds in particular share similar habitats e.g., mangroves, coral reef ecosystem, intertidal areas, lagoons and rocky shores. It is important to learn and be able to distinguish between them. “If you take seagrasses away to identify, make sure take the “whole plant” – a complete cluster of shoots with rhizomes, roots and if available the flowering plants. If just a shoot is collected, not only you may miss the flowering materials but you may find that you do not have all the information that you require”. Accurate species identification in the field would be helpful and allow more people to understand and appreciate seagrasses. This is especially true where people now are very much aware on its unique natural values e.g., especially seagrass beds provide habitats and feeding ground for dugongs, green turtles, seahorses and other invertebrates. Are seagrasses merely green vegetation along the coastline? Seagrasses do much more than providing underwater spectacular scenes. The lush vegetation in a seagrass bed (e.g., Sungai Pulai estuary and its adjacent waters) may harbor hundreds of species and each is unique and interconnected in a food web. In this case the heart of a food web is the seagrasses, providing food and oxygen. A food web is strong when intact, yet easily disturbed and each disrupted connection weakening the web. We must recognize the value of all species and the hidden relationship between them. This lecture provides the basis for far more work on the seagrasses and their associates.